Development of a guar gum film with lysine clonixinate for periodontal treatments - Robles-Kanafany, Casandra Marilú; Del Prado-Audelo, María Luisa; González-Torres, Maykel; Giraldo-Gomez, David M.; Caballero-Florán, Isaac H.; González-Del Carmen, Manuel; Sharifi-Rad, Javad; Figueroa-González, Gabriela; Reyes-Hernández, Octavio D.; Cortés, Hernán; Leyva-Gómez, Gerardo (Cellular and Molecular Biology, 2021)
Periodontal pain is a public health problem derived from different conditions, including periodontal diseases, prosthetic complications, and even extractions performed by dentist. There are various treatments to control acute dental pain, being the administration of analgesics, such as Lysine Clonixinate (LC), a common practice. Unfortunately, higher and repeated dosages are usually required. The purpose of this work was to develop a prolonged release pharmaceutical form as an alternative treatment for dental pain. Hence, we conceived a film based on guar gum and loaded different concentrations of LC. We evaluated the film's appearance, brittleness, strength, and flexibility, and then chose one formulation for adequate characteristics. Subsequently, we assessed the morphology, thermal behavior, and swelling properties of the films (LC-free and –loaded). Finally, we performed the release studies of LC from the films in vitro using a simulated saliva medium and employed several mathematical models to evaluate the release kinetics. Guar gum is a natural polymer obtained from the endosperm of Cyamopsis tetragonolobus that presents properties such as biosafety, biocompatibility, and biodegradability. Thus, it represents a potential excipient for use in pharmaceutical formulations. Moreover, our results revealed that the LC-loaded film presented a high adherence, suitable swelling behavior, high LC content, and a prolonged drug release. Therefore, the LC-loaded film may be considered a potential option to be applied as an alternative to treat dental pain.